The Long Twentieth Century: The Great Divergence; Hegemony, Uneven Development, and Global Inequality - Paderanga Jr., Cayetano (Kasarinlan: Philippine Journal of Third World Studies, 2008)
Review of The Long Twentieth Century: The Great Divergence; Hegemony, Uneven Development, and Global Inequality
Keywords: Hegemony, Uneven Development; Global Inequality